Robust decentralized power oscillation dampers design of DFIG wind turbines for stabilization of inter-area oscillation - Surinkaew, Tossaporn; Ngamroo, Issarachai (My University, 2014)
A new decentralized power oscillation dampers (POD) design of doubly-fed induction generator (DFIG) wind turbines for damping of inter-area oscillation is presented in this paper. The practical 2nd-order lead/lag compensator with single input signal is used for the POD structure. The POD is equipped with the voltage controller of rotor side converter of DFIG. With the damping signal from POD, the reactive power output of DFIG can be modulated to damp out the oscillations. The parameters optimization of decentralized PODs is conducted over a wide range of tie-line power flow levels so that the damping performance of PODs can be enhanced. The improved firefly algorithm is used to achieve the optimal POD parameters automatically. Study results in a two-area four-machine interconnected system show that the stabilizing effect of proposed decentralized POD is higher than the conventional POD under severe faults, heavy power flows, and wind speeds. © 2014 IEEE.
Keywords: Doubly-fed induction generator; firefly algorithm; inter-area oscillation; power oscillation damper